The Implementation of Risk Assessment in the Context of Implementing Enterprise Risk Management (ERM) at PT. Solusi Bangun Indonesia Tbk - Sutarsa, Richi Gunandi (Budapest International Research and Critics University, 2022)
The aims of this study are to find out the Implementation of Risk Assessment in the Context of Implementing Enterprise Risk Management (ERM) at PT. Solusi Bangun Indonesia Tbk. This research uses a qualitative research approach in which qualitative research is often used to research in the field of social sciences and to problems that cannot be examined quantitatively. Based on the discussion above it can be concluded that: 1.In accordance with the data and observations obtained by researchers, the implementation of risk assessment in the Company has not been effective enough because there is still a shortage of risk assessors in terms of risk management knowledge, lack of awareness of control and risk on both the risk owner and RTU sides and also a lack of attention from upper management levels, so that the risk assessment process takes place arbitrarily (nice to have). 2. Several factors that become obstacles or obstacles to the running of the risk assessment process are also due to the pandemic conditions which require the process to run through the virtual, where the virtual process has weaknesses.